Preparedness for Mitigating Noncommunicable Diseases in Gaindakot Municipality, Nepal: Perspectives of Key informants - Sapkota, Narayan; Paneru, Damaru Prasad (Birat Journal of Health Sciences, 2021)
Introduction: Non-communicable Diseases (NCDs) are the major public health problem that leads to high morbidity and mortality in the world including Nepal. Government of Nepal has launched the Multi-sectoral NCD Action Plan in 2014 and established NCD and Injuries Poverty Commission in 2016 for the management and control of NCDs nevertheless the implementation status and its outcomes are not identified till date at the local level.Objectives: To explore the preparedness of the local government for the prevention and control of NCDs at Gaindakot, Nawalpur, Nepal.Methodology: A qualitative study was conducted in the Gaindakot municipality; Nawalpur to document the key informant's perspectives on health system's preparedness to prevent the potential impacts of NCDs. Face to face Indepth interview was performed using open-ended questions. Interview guidelines were prepared on the basis of building blocks of health system. Information was processed basis on thematic analysis.Result: The study revealed that health section has NCD preparedness structure but need to strengthening for the better delivery of health services. The study highlights that screening services and the medicine for major NCDs like hypertension and diabetes were available at local level. Limited budget was allocated and health workforce was not trained for NCDs prevention and control. There was no reporting mechanism for NCD related data from local level.Conclusion: Basic medicine and screening services were provided from the local level to the selected NCDs such as hypertension and diabetes. There was no provision of reporting NCD related information and health workforce were not trained to respond NCDs. Local level health system strengthening is an urgent need to address the increasing burden of NCDs.